Factors Affecting Consumers’ Decision to Purchase Residential Properties with Product Innovation in Nonthaburi Province. - ขุนศรีแก้ว, ธีระยุทธ์; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: 1) study the demography factors influencing purchasing decision of residence with product innovation in Nonthaburi Province 2) study the consumers’ behavior in purchasing decision of residence with product innovation in Nonthaburi Province. The sample group in this research was 400 population with the age over 25 living in Nonthaburi Province. The questionnaire was used to collect data. The descriptive statistics were frequency, percentage, mean and standard deviation and the influential statistics were t-test and One-Way ANOVA.          The results of this research revealed that mostly of the sample group was female with the age between 31-35, bachelor’s degree, private employees, average income per month between 20,001-30,000 baht. The behavior in purchasing decision of residence mostly was in purchasing a single house with the cost of 2.01-4 million baht. The main purpose in purchasing residence depended on family separation. The internet was used to find the information including with the web site. The influential person towards the purchasing decision was self-determination.The place where the samples made decision to buy a house was the sales office. The result also showed that the occupation related with purchasing decision of residence with product innovation of consumers in Nonthaburi Province was statistical significance at .05 level while gender, age educational background and income did not relate with purchasing decision of residence with product innovation of consumers in Nonthaburi Province.